Anti-cancer study of Ni (II) and Zn (II)- chitosan complexes - Beyadir R. Abed; Ali O. Mohammed (Tikrit Journal of Pure Science)
Two neutral chitosan polymer complexes with Ni(II) and Zn (II) were prepared and characterized by molar conductivity measurements, IR spectroscopy. The prepared complexes were tested against two types of cancer cell lines {breast cancer (MCF-7) and ovarian cancer (A2780)}. That the Ni-chitosan complex was significantly active then the Zn-chitosan complex with IC50 value is 167.67± 4.6 mg/ml for (MCF-7) and 200.45± 8.23mg/ml for (A2780). Whereas IC50 value of Zn-chitosan complex 189.03± 3.7mg/ml for (MCF-7) and 231.70± 5.25mg/ml for (A2780)